Penyelesaian Metode Round Off dan Metode Cutting Plane dalam Optimalisasi Produksi Anyaman Rotan UD. Kirana - Safitri, Elfira; Basriati, Sri; Mexdika, Raja Putra; Soleh, Mohammad (UIN Walisongo Semarang, 2024)
UD Kirana is a trading business that produces rattan weaving in Rumbai district which consists of 5 types of products produced, namely guest chairs, terrace chairs, tender chairs, serving hoods and baskets. In the rattan woven production process, UD Kirana cannot predict how many items can be produced each week so that maximum profits have not been achieved.This research aims to find out how goods can be produced every week in order to get maximum profits.The methods used are the Round Off method and the Cutting Plane method. Based on the research result, UD Kirana produced 10 tender chairs, 7 serving hoods and 21 baskets with a profit of Rp. 6.060.000. The Round Off method is more efficient than the Cutting Plane method, this can be seen from the addition of constraints, namely the Round Off method adds two constraints and the Cutting Plane method adds three constraints or gomory constraints.